SPHERICAL CRYSTALLIZATION A NOVEL APPROACH FOR SOLUBILITY AND DISSOLUTION ENHANCEMENT OF SIMVASTATIN - PARMAR SHITAL S; MISHRA RAKESH; SHIROLKAR SV (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Simvastatin is commonly used antihyperlipidemic in the treatment of hypercholesterolemia and dyslipidemia. As evidenced form the scientific investigation, it is reported for its lower solubility and poor dissolution rate. The aim of the present investigation was to develop simvastatin spherical agglomerates to improve its solubility and dissolution characteristics by spherical agglomeration method. The crystallization media used was methanol, water and chloroform as bridging liquid and PVP K-30 as a polymer. The process variables such as amount and type of (bridging liquid and polymer), stirring speed and stirring time were optimized and reported. The spherical agglomerates were further subjected for determination of % drug content, particle size analysis, solubility and dissolution rate. The agglomerates were also characterized by Differential Scanning Calorimetry (DSC), Fourier Transform Infrared Spectroscopy (FTIR), and X-ray Powder Diffraction (XRD) analysis and affirmed. Among the entire parameters spherical agglomerates obtained with methanol (7ml), water (50ml), chloroform (1.5ml) and PVP K-30 (0.5%) showed improvement in solubility and dissolution rate in comparison with pure drug. The spherical agglomerates showed significant improvement in dissolution from a value of 25.53% for pure simvastatin to 91.31% of spherical agglomerate. The spherical agglomerates of optimized batch were directly compressed and dissolution profile was compared with marketed tablet. Such a technique can successfully be employed to improve solubility and dissolution characteristic of poorly soluble drugs.